The prevalence of antral exostoses in the maxillary sinuses, evaluated by cone-beam computed tomography - Meryem Toraman Alkurt; Ilkay Peker; Oguzhan Demirel; Gulsun Akay; Kahraman Gungor; Ozlem Ucok (Elsevier, 2016)
Background/purpose: Exostoses are outgrowths of normal compact and cancellous bone and may occur in different locations of the jaw. Exostoses are a rare anatomic variation in the maxillary sinuses. The purpose of this study was to investigate retrospectively the prevalence of location, size, shape, and symmetry of exostoses in the maxillary sinus, and to assess the relationship between demographic variables (i.e., age and sex) via cone-beam computed tomography images. Materials and methods: Cone-beam computed tomography images of 1000 patients [521 (52.1%) females and 479 (47.9%) males], aged 10-85 years (mean age, 44 years), were examined. Two investigators examined the exostoses for location (i.e., inferior wall, medial wall, lateral wall, or posterior wall of the maxillary sinuses), size, shape (i.e., broad-based or mushroom-like), and symmetry (i.e., unilateral or bilateral). The age of the patients was categorized into three groups: 10-30 years, 31-50 years, and 51+ years. The data were statistically analyzed by using chi-square test, Fisher's exact test, and the t test. Results: In total, 52 exostoses from 48 patients (4.8%) were identified. Exostoses were more common in females (n = 28, 58.3%) than in males (n = 20, 41.7%); however, there was no statistically significant difference between the sexes (P > 0.05). The presence of exostoses was very similar for all age groups with no statistically significant differences (P > 0.05). Conclusion: Most exostoses were unilateral and on the inferior wall of the maxillary sinus. No statistically significant difference existed between the frequency and location of exostoses for sex or age groups (P > 0.05).